1999
DOI: 10.1023/a:1006960106929
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was carried out to evaluate whether curcumin, a potent antioxidant, had any specific role in the synthesis and degradation of collagen in rat heart with myocardial necrosis, induced by isoproterenol.HCI (ISO). Myocardial necrosis was induced by administration of ISO (30 mg/100 g body weight subcutaneously twice at an interval of 24 h) and studies on collagen metabolism were carried out with curcumin (200 mg/kg) pre-and co-treatment with ISO. The incorporation of 14C-proline into collagen was studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Myocardial edema, necrosis, and inflammatory cells are the reasons for the cardiac hypertrophy observed in myocardial infarcted rats. [ 26 ] Administration of β‐caryophyllene repressed the occurrence of cardiac hypertrophy in myocardial infarcted rats, by its anti‐cardiac hypertrophic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial edema, necrosis, and inflammatory cells are the reasons for the cardiac hypertrophy observed in myocardial infarcted rats. [ 26 ] Administration of β‐caryophyllene repressed the occurrence of cardiac hypertrophy in myocardial infarcted rats, by its anti‐cardiac hypertrophic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin has also proven its efficacy in protecting rat myocardium from myocardial ischemic injury induced by isoprenaline (Nirmala and Puvanakrishnan, 1996; Manikandan et al, 2004). These beneficial effects of curcumin were mainly associated with its ability in ROS scavenging and the inhibition of lysosomal enzymes (Nirmala et al, 1999). Treatment with curcumin also exhibited beneficial effects in kidney damage by limiting the expression of Fas-L and Fas (Jones et al, 2000).…”
Section: Other Potential Effects Of Curcuminmentioning
confidence: 99%
“…Bleomycin treatment significantly increased the HYP content of the lung by generating free radicals (20) while curcumin blocked the formation of toxic free radicals, which in turn could significantly decrease HYP production. Also, curcumin can modulate collagen metabolism (21). Unlike oral curcumin administration and curcumin inhalation, our data showed that the inhalation of the synthesized nano-curcumin could restore lung HYP content.…”
Section: Discussionmentioning
confidence: 80%